If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + 3s = 66 Reorder the terms: 3s + 6t = 66 Solving 3s + 6t = 66 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-6t' to each side of the equation. 3s + 6t + -6t = 66 + -6t Combine like terms: 6t + -6t = 0 3s + 0 = 66 + -6t 3s = 66 + -6t Divide each side by '3'. s = 22 + -2t Simplifying s = 22 + -2t
| (1/x)-4x=0 | | 1/x-4x | | 1/x-4x0 | | (3r-5v)(7r+4v)= | | Y=(-2x+5)(x+3) | | -20(x-2)=10 | | (x-2)(3/4)=8 | | x+16y=6920 | | 3+x=404 | | Y=(2k+1)(k-4) | | 37=7.5 | | Y=51x^2-44x+5 | | Y=5k^2(-6k^2-2k+6) | | 2(5x+15)=33 | | 7(12+8)-6=9(7T+2)-T | | 2x(5/3)=-64 | | 3x+6=7+3x | | Y=-x(6x-7) | | 2x+3=3c-4 | | 200/20*5 | | -2n^2=-3n-14 | | 24v^6w^7-30v^2w^5y^9=0 | | Y=8t^5*8t^5 | | 4^x−2=(1/16)^4x−3 | | 8+K=8 | | 42=40 | | 3m+3+1+2m= | | (x^2)-6x+3=0 | | 18=8(4x+1) | | 2x-1=5x+13 | | 30=2 | | 8M-(7M+5)=-8-(M+12) |